Mangrove Canopy Cover Analysis Using Hemispherical Photography in Muara Jeruju Village, Kubu Raya Regency, Indonesia - Iwan Kuncoro; Ahmad Albar; Lefdi Agung Nugraha (Universitas Teuku Umar, 2026)
Muara Jeruju Village is an estuarine ecosystem influenced by the Kapuas River and anthropogenic activities of coastal communities in Kubu Raya Regency, Indonesia. These conditions generate considerable variability in mangrove growth dynamics. This study aims to quantify mangrove canopy cover using the Hemispherical Photography (HP) method as an indicator of ecosystem health. Data were collected from three stations representing the riverfront, middle, and hinterland zones, with a total of 15 hemispherical photographs (5 images per station) used as sampling units. Hemispherical images were processed using ImageJ software to estimate canopy cover percentages, which were subsequently classified according to the standards of the Geospatial Information Agency (BIG, 2014). The results indicate that canopy cover was 58.4 ± 1.85% in the riverfront zone, 72.8 ± 1.48% in the middle zone, and 65.1 ± 1.67% in the hinterland zone, indicating moderate to dense canopy categories. No sparse canopy class was identified across all stations. Overall, the mangrove ecosystem in Muara Jeruju Village can be categorized as being in moderate to dense condition based on canopy cover values (58.4–72.8%) according to the classification standard of the Geospatial Information Agency (BIG, 2014). However, the riverfront area experiences relatively higher environmental pressure due to sedimentation processes and water transportation activities.